Uniform Convergence of Schwarz Method for Elliptic Quasi-Variational Inequalities Related to Impulse Control Problem - Mohamed Haiour; Salah Boulaaras (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
In this paper we provide a uniform convergence using an overlapping Schwarz method on nonmatching grids for quasi-variational inequalities related to impulse control problem. The discretization on every sub-domain converges in uniform norm was provided and a result of approximation in the -norm was given.